Dead or alive - McGarrity, Michael (Dutton, 2008)
Retired Santa Fe police chief Kevin Kerney is horrified to learn that his horse-training partner, Riley Burke, has been murdered by an escaped prisoner, prompting Kerney to team up with his half-Apache son to hunt down the killer.